ANALISIS FAKTOR YANG MEMPENGARUHI PRODUKSI DAN RISIKO USAHA TANI GARAM DI KABUPATEN JENEPONTO (STUDI KASUS DESA ARUNGKEKE, KECAMATAN ARUNGKEKE) - Sitti Rahbiah; Andi Maslia Tenrisau Adam; Muhammad Nurul Ashari; Muhammad Hattah Fattah; Muhammad Fiqih Oktavian Hattah (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2024)
One of the natural potentials in coastal areas is the salt business. Salt (NaCl) is a food supplement and a source of electrolytes for the human body. The study aims to: (1)Describe the salt production process; (2)Analyze the factors that affect salt production; (3)Analyze the production and income of salt farmers; (4)Analyze the production and income risks faced by salt farmers. The study population was all salt farmers in Arungkeke Village, Jeneponto Regency, totaling 161 people. Determination of the number of farmer samples using the Slovin Method with 35 respondents by simple random sampling. The data analysis method is Descriptive Analysis, Multiple Linear Regression Analysis, Income Analysis and Risk Analysis. The results of the study show that: (1)The salt business production process is by land processing, adding sea water, water evaporation, and harvesting is carried out every 7-8 days. (2)The influence of capital production factors(X1), number of workers(X2), land area(X3), length of work(X4), and sea water volume(X5) together (F test= 17.438) is significant. The R-square value of 0.750 means 75% influence of model X1-X5 on the research results. Partially (t-test) then X1, X3, X4 and X5 are significant, while X2 is not significant. (3)The average Total Salt Production/Farmer is 8,787.42 Kg or 107.164 Kg/Ha. While the Average Farmer Income is Rp.21,655,688 or Rp.64,093,757/Ha. (4)The level of Production Risk faced by salt farmers is classified as high because the coefficient of variation (CV) value is 1.21(>0.5). Meanwhile, the income risk level is also high because the CV value is 2.13(>0.5).